9514 1404 393
Answer:
a, c, b
Step-by-step explanation:
Collect terms, subtract the constant, divide by the y-coefficient.
(a) 4y + (y - 1) = 29 ⇒ y = 6
(c) (2y + 3) - 4 = 9 ⇒ y = 5
(b) 4y - y + 1 = 13 ⇒ y = 4 . . . . . this equation is not what you have written
__
<em>Additional comment</em>
The second equation suffers from a typo, so your answer may vary.
2 ( k-5) 13 you don't need two k-5 you can simplify it so you just know to do it twice
Answer:
bleh bleh bleh hehebeiejhsievdudveusvsgzyvehs
Answer:
$702.53
Step-by-step explanation:
178.74
36,52+18.92+25.93=81.37
178.74-81.37=97.37
300+100+205.16=605.16
605.16+97.37=702.53
The final balance is 702.53 dollars.
Answer:
(two sixths)
Step-by-step explanation:
if we scale the fraction 1 / 3 to find equivalent fractions, we can simply multiply both numbers by the same factor.
So, by multiplying both 1 and 3 by two, we will have an equivalent fraction
1 × 2 = 2
_ _
3 × 2 = 6
This means that
(one third) is equivalent to
(two sixths)